Fiscal policy in real time - Jacopo Cimadomo (European Central Bank (ECB), 2008)
This paper argues that any assessment on the intentional stance of fiscal policy should be based upon all the information available to policymakers at the time of fiscal planning. In particular, real-time data on the discretionary fiscal policy "instrument", the structural primary balance, should be used in the estimation of fiscal policy reaction functions. In fact, the ex-post realization of discretionary fiscal measures may end up to be drastically different from what was planned by fiscal authorities in the budget law. When fiscal policy rules are estimated on real-time data, our results indicate that OECD countries often planned a counter-cyclical fiscal stance, especially during economic expansions, whereas conventional findings based on revised data point towards pro-cyclicality. This finding calls into question the effectiveness of discretionary fiscal policies to fine tune the business cycle, as (pro-cyclical) actual outcomes tend to deviate from (counter-cyclical) fiscal plans. Furthermore, we test whether threshold effects might be at play in the reaction of fiscal policy to the economic cycle and to public debt accumulation. It emerges that the intended cyclical behavior of fiscal policy is characterized by two regimes, and that the switch between them is likely to occur when output is close to its equilibrium level. On the other hand, the use of revised data does not allow to identify any threshold effect.
Keywords: C23; E30; E62; H30; H60; 330; endogenous threshold models; Fiscal Policy; real-time data; revision errors; Finanzpolitik; Politische Entscheidung; Informationsversorgung; Schätzung; OECD-Staaten